Design and Development of a Wearable Device for Monitoring Social Distance using Received Signal Strength Indicator - Cunha, André Oliveira; Loureiro, Joana Venturin; Guimarães, Rodrigo Laiola (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
This paper presents the prototype of a compact and low-cost wearable electronic device that, based on the reading of the Wi-Fi signal strength emitted by other wearable devices of the same type, estimates the proximity between users and issues a notification (an audible and visual alarm) when the distance between them is less than a reference value. Our preliminary results suggest that the proposed solution may be a viable alternative to ensure social distancing as a practice to face the pandemic caused by COVID-19.